Exploring the Factors that Impact Access to Senior High Education among Youth in Upper Malubog, Manticao, Philippines - Selma, Ediepearl; Jumamil , Chezyl Jade R; Sayson , Roel S (Golden Ratio of Social Science and Education, 2024)
This research study was undertaken primarily to explore the factors that impact access to senior high education among youth in Upper Malubog, Manticao, Misamis Oriental, Philippines. It intends to give importance to education in the said community. This study used a mixed-method research design. A quantitative method is used to describe the demographics and socio-economic profile of the respondents and the factors affecting their access to senior high education. A qualitative method is also employed to dig deeper into the challenges that hinder the school in offering senior high school from the teachers’ perspectives, and the respondents’ suggestions and recommendations to improve access to senior high education. The quantitative data was collected through an interview schedule of thirty out-of-school youth, aged 16-30, while the qualitative data was collected through a key informant interview with five high school teachers of Malibato Integrated School.  Based on the findings, the following implications are formulated: This study does not only focus on one factor, but five different factors which are the school and environmental, economic, family-related, peer, and personal factor. Youth’s access to senior high education was impacted by these mentioned factors, however, they were most affected by economic and school, and environmental factors.